Plant–fungi interactions in Marchantia polymorpha are associated with horizontal gene transfer and terpene metabolism - Karima El Mahboubi; Chloé Beaulieu; Baptiste Castel; Cyril Libourel; Nathanaël Jariais; Emilie Amblard; Fabian van Beveren; Jean Keller; Yves Martinez; Jessica M. Nelson; Maxime Bonhomme; Christophe Jacquet; et al. (Proceedings of the National Academy of Sciences, 2026)
The liverwort Marchantia polymorpha has emerged as a model for studying plant immunity in bryophytes, providing unique insights into conserved defense mechanisms across land plants. By contrast, Marchantia-specific immune mechanisms remained largely underexplored. In this study, we investigated the genetic basis of quantitative resistance in M. polymorpha against the fungal pathogen Colletotrichum nymphaeae , a naturally occurring compatible parasite. Through a combination of phenotypic, cytological, and transcriptomic approaches, combined with genome-wide association studies (GWAS), we identified key defense-related genes and pathways. Leveraging the biological and genetic variability present in a collection of natural M. polymorpha accessions, we highlight the role of horizontally transferred microbial-like terpene synthase genes, which may contribute to the exceptional terpene diversity of liverworts and potentially play a role in pathogen resistance. GWAS uncovered candidate loci associated with resistance traits, implicating both core immune components and specialized metabolic pathways. Transcriptomic analyses performed on two accessions with contrasting phenotypes after inoculation with C. nymphaeae revealed the upregulation of accession-specific and horizontally acquired genes. These results provide insights into the specific molecular underpinnings of bryophyte immunity and underscore the evolutionary significance of horizontal gene transfer and specialized metabolites in shaping plant–pathogen interactions.